Creditor protection laws, debt financing, and corporate investment over the business cycle - Qi, Yaxuan; Roth, Lukas; Wald, John (Journal of International Business Studies, 2017)
We examine how legal creditor rights are related to debt financing and corporate investment over the business cycle. Using firm-level data from 40 countries, we find that creditor rights are associated with greater debt financing and investment during economic downturns, but creditor rights have a significantly smaller effect during expansions. The beneficial effects of creditor rights during recessions are stronger for firms that are more likely to have severe shareholder–bondholder agency problems. We also find that during recessions (relative to expansions) strong creditor rights are associated with a smaller decline in net capital flows. Our findings are consistent with credit market frictions increasing during recessions, and with stronger creditor rights decreasing the negative effects of these frictions. Overall, the results suggest that better creditor protection laws help moderate the decline in debt financing and investment during recessions.